2001
DOI: 10.1016/s0032-9592(01)00219-9
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and operational response of an anaerobic fixed bed digester to oleic acid overloads

Abstract: The effect of oleic acid overloads on biomass accumulation and activity in an anaerobic filter was investigated. An anaerobic fixed-bed reactor specially designed to allow the regular withdrawal of accumulated biomass was used for that purpose. Organic and hydraulic shocks were performed during four days, by stepwise increasing the substrate concentration from 4000 to 20 000 mg COD/l or by reducing the hydraulic retention time from 16 to 3.2 h. During the organic shock, operational performance was more affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 19 publications
0
17
1
Order By: Relevance
“…Adaptation of acetotrophic methanogens in continuously operated systems has previously been observed Cavaleiro et al, 2001). Cavaleiro et al (2001) found that a hydraulic shock (reduction of HRT) of oleate to an anaerobic filter induced an increase in the tolerance.…”
Section: Adaptation Of Microorganisms To Oleatementioning
confidence: 91%
See 3 more Smart Citations
“…Adaptation of acetotrophic methanogens in continuously operated systems has previously been observed Cavaleiro et al, 2001). Cavaleiro et al (2001) found that a hydraulic shock (reduction of HRT) of oleate to an anaerobic filter induced an increase in the tolerance.…”
Section: Adaptation Of Microorganisms To Oleatementioning
confidence: 91%
“…However, continuous experiments with fixed-bed reactors have showed that pre-exposure of acetotrophic methanogens to lipids benefits the development of resistance to oleate . Cavaleiro et al (2001) found that a hydraulic shock (reduction of HRT) induced an increase in the resistance of acetotrophic methanogens towards oleate; whereas an organic shock of oleate (increase in substrate concentration) resulted in a lower resistance towards oleate.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…LCFA overloading has been shown to lead to volatile fatty acid (VFA) and LCFA accumulation that may significantly reduce methane production due to imbalances between acid consuming and methane producing microorganisms Angelidaki and Ahring 1992;Eiroa et al 2012;Rinzema et al 1994). Overloading of LCFA can cause concentrations of total volatile acids to be above 2000 mg COD/L or more and/or acetate concentrations above 500 mg COD/ L (Cavaleiro et al 2001;Cavaleiro et al 2009;Eiroa et al 2012). As the total calculated amounts of COD (<55 mg COD/L) and acetate (<15 mg COD/L) produced in this study for microcosms containing biodiesel are much less, they should not be inhibitory.…”
Section: Effects Of the Presence Of Biodiesel In The Anaerobic Degradmentioning
confidence: 99%